Comparison of sedentary time, number of steps and sit-to-stand-transitions of desk-based workers in different office environments including working from home: analysis of quantitative accelerometer data from the cross-sectional part of the SITFLEX Study - Martha Sauter; Eva Backé; Carina Pfab; Michaela Prigge; Claudia Brendler; Falk Liebers; Peter von Löwis; Andrea Pfeiffer; Falko Papenfuss; Janice Hegewald (Scandinavian Journal of Work, Environment & Health)

(untitled)
OBJECTIVES: Sedentary behavior is associated with diseases (eg, cardiovascular, diabetes type 2). We aimed to describe the sitting and moving behavior of desk-based hybrid employees of a large company in Germany working in either a traditional open plan office (OPO) or an activity-based flex office (AFO) and when working from home. We also aimed to determine if the behaviors differ between both working environments (ie, working from home versus the office) and the office concepts (OPO versus AFO). METHODS: We conducted a cross-sectional study to measure sedentary time, sit-to-stand-transitions (STS), standing, and physical activity (time spent physically active and steps) in different working environments with activPAL3. Time-use data were also examined using compositional data analysis. Mixed model regression was performed to estimate means and 95% confidence intervals (CI). The main models were adjusted for sex, age, profession and measurement phase (July–November 2021). RESULTS: The sample comprised 102 employees (women: N=27, mean age 38.9 years). On average, OPO employees spent 351 minutes (95% CI 322–380) being sedentary, took 2763 steps (95% CI 2460–3066) and made 16.6 STS (95% CI 13.6–19.6). AFO workers averaged 333 sedentary minutes (95% CI 308–358), 2906 steps (95% CI 2645–3167) and 19.1 STS (95% CI 16.6–21.7). When working from home, workers spent 378 minutes (95% CI 359–396) being sedentary, took 1257 steps (95% CI 1063–1452) and made 20.9 STS (95% CI 19.0–22.8). Working from home was associated with increased sedentary time and fewer steps but more STS. CONCLUSION: Sedentary time of desk-based workers seems to be prolonged when working from home. As sedentary behavior increases the risk of disease, there is a need for measures to reduce employees` sedentary time in all working environments.